APPlied stalking: What the next generation of stalking victims consider to be 'stalking' and why victims report their experiences to the police. (January 2023) - Brady, Patrick Q.; Reyns, Bradford W.; Landhuis, Jennifer; Griffin, Vanessa Woodward
Abstract: Research suggests that offenders are finding new ways to exploit the conveniences of commonplace technologies for malicious purposes. What is less clear is whether targets of the malicious conduct consider emerging forms of technology-facilitated (TF) abuse as 'stalking' and whether such tactics influence decisions to involve the police. Using a national sample of emerging adults (ages 18–24) meeting legal criteria for stalking ( N = 194), the current study investigated whether victim decision-making was related to pursuit type (physical only, TF-tactics only, both), the number of different tactics, and/or the frequency of specific pursuit behaviors. Net of victim and situational considerations, stalking acknowledgement was solely related to the frequency of being followed. Victims who were frequently followed were more likely to identify their experience as stalking while relentless threats and harassment via Snapchat produced a 12% decrease in the odds of acknowledgement. The findings suggest the need for adapting stalking prevention initiatives to discuss technology-facilitated pursuit tactics while increasing the capacity of first responders to identify and collect digital evidence.